Changes during Cooking Processes in 6 Varieties of Andean Potatoes (Solanum tuberosum ssp. Andinum) - Jimenez, María Eugenia (2015)
The value of the native potato varieties grown in Argentinean northwest lies both in their fundamental role as a source of food for the population and in their potential for the development of new products. The aim of this work was to study the changes produced by two common cooking processes (boiling and frying) on the nutritional, textural and functional characteristics of five Andean potatoes varieties. The cooking process (boiling) does not significantly affect the composition of potatoes, but there are losses of vitamin C; a greater loss was observed when they were boiled shelled. In frying potatoes vitamin C is completely destroyed. Resistant starch values between 0.90 and 4.58 g/100g of potato were found for raw Andean varieties; they decreased during the cooking process (boiled) (0.15 to 0.54 g/100g of potato) and increased again to be stored for 48 h at 4°C (0.73 - 1.88 g/100g of potato). The frying process produced an increment in energy value between 92% and 148% according to variety. Regarding to the fracture strength and hardness, no significant differences were observed between the Andean varieties and the control (Spunta) at the initial or final stages, but there were differences during the intermediate stages.